Impact of different treatment strategies on therapeutic efficacy and biomarkers in children with IVIG-resistant Kawasaki disease: a retrospective cohort study - Zhou, Xin; Dong, Rui; Wei, Xiaoling; Ding, Hao; Wang, Xiaochen; Wu, Wei; Kang, Guiyun; Li, Lei; Ma, Xiang (Frontiers in Pharmacology, 2025)
BackgroundIntravenous immunoglobulin (IVIG) is the standard first-line treatment for Kawasaki disease (KD), although 10%–20% of patients are resistant to initial IVIG therapy. This study investigates retreatment strategies and associated biomarkers in IVIG-resistant KD patients.MethodsThis retrospective analysis included 68 IVIG-resistant KD patients from the Children’s Hospital Affiliated to Shandong University. Patients were categorized into three retreatment groups: glucocorticoids (GC) (Group A), IVIG retreatment (Group B), and combination therapy (Group C). Clinical characteristics, laboratory parameters, and therapeutic outcomes were compared, with multivariate logistic regression identifying biomarker correlations.ResultsDespite significant differences in pre-treatment levels of C-reactive protein (CRP) and alanine aminotransferase (ALT) across groups, the combined overall response rate for all three groups following different retreatment strategies exceeded 98%. Multivariate logistic regression analysis identified pretreatment eosinophil percentage (EOS%) and albumin (ALB) levels as independent predictors of favorable outcomes, while elevated CRP was significantly associated with adverse outcomes. Furthermore, an increase in EOS% was observed after IVIG retreatment, suggesting a possible modulation of T helper 2 (Th2) immune responses by this intervention. Changes in coronary artery dilation further supported the potential benefits of GC monotherapy and combination therapy in mitigating acute vascular injury.ConclusionBoth GC and IVIG, either alone or in combination, are effective treatments for IVIG-resistant KD. EOS%, CRP, and ALB may serve as independent prognostic markers in children with IVIG-resistant KD, providing a foundation for personalized retreatment strategies.